A socio-ecological framework of social justice leadership in education. Issue 3 (29th April 2014) - Berkovich, Izhak
Abstract : Purpose: – The purpose of this paper is to present the gap between conceptualizations of social injustices and the desired social transformation that addresses multiple social subsystems and levels on one hand, and social justice leadership that addresses intra-school efforts on the other. The paper aims to expand the conceptualization of social justice leadership and tie it together with concepts of activism and social change. Design/methodology/approach: – The paper adopts a socio-ecological perspective. It reviews works about social justice leadership in education, activism, and social change to present the notion that in light of existing social justice barriers educational leaders should serve as activists in schools and in the community and policy areas. Findings: – The paper presents a macro framework, focussing on individual leaders in the field and on the consolidation of intentions, actions, and outcomes in a manner necessary for using social justice as an effective socio-political agenda in a socio-ecological system. Originality/value: – The paper presents a conceptual framework which can enable practitioners and researchers to better understand social justice efforts.